Investigating the Association Between Lower Extremity and Low Back Symptoms Among Saskatchewan Farmers Using the Standardized Nordic Questionnaire. Issue 19 (1st October 2017) - Essien, Samuel Kwaku; Trask, Catherine; Dosman, James; Bath, Brenna
Abstract : Study Design: Cross-sectional survey. Objective: The aim of this study was to investigate the association between self-reported low back symptoms and symptoms in the hip, knee, and ankle in a high-risk occupational group. Summary of Background Data: Low back pain, with or without lower extremity referral, poses a major challenge to occupational productivity, especially in farming. Although low back symptoms can occur independent of lower extremity symptoms, anatomical positioning of nerves supplying the lower limbs means structural and physiological changes in the spine can lead to referred pain in the lower limbs, but the magnitude of the association between low back and lower extremity symptoms is unclear. Methods: Baseline postal questionnaire data from the Saskatchewan Farm Injury Cohort Study yielded surveys from 2653 adults from 1020 farms, who responded to Standardized Nordic Questionnaire (SNQ) items on "ache, pain, discomfort" in nine body parts during the last 12 months. Bivariate and multivariate regression modeling was performed with low back symptoms as the outcome and lower extremity symptoms as the independent variable. Results: After adjustment for age, sex, depression, and heavy lifting, low back symptom was significantly related with hip pain (odds ratio [OR] = 3.84, 95% confidence interval [CI] 3.04–4.84), knee pain (OR = 1.84, 95% CI 1.49–2.28), and ankle pain (OR = 1.79, 95% CI 1.40–2.29). Results showed a significant but decreasing relationship to low back symptoms as sites became more distal. Conclusion: Hip and low back symptoms are highly associated, suggesting a common mechanism may be at work. Although there appears be increased risk of knee and ankle region symptoms among those with back pain, the SNQ is not designed to differentiate types of referred symptoms ( i.e., numbness, tingling, shooting pain) and/or clinical diagnoses. Other tools, possibly corroborated with clinical examination findings, are likely necessary for a more thorough investigation of referred pain patterns in this high-risk occupational group. Level of Evidence: 3